Service Quality Dimension during Open and Distance Learning (ODL) in UiTM - Ariffin, Syahrul-Niza Kamarul; Muhamat, Amirul Afif; Jaafar, Muhammad Nizam; Abdul Karim, Norzitah (Information Management and Business Review, 2023)
This study investigates how students in the Faculty of Business and Management at UiTM perceive the service quality dimensions of their lecturers during Open and Distance Learning (ODL). The study is unique because it is the first time UiTM implemented Open and Distance Learning (ODL) instead of the usual face-to-face learning, due to the Malaysian government’s instruction of Movement Control Order (MCO). The servqual model is used to calculate service quality dimensions such as reliability, responsiveness, assurance, empathy, knowledge, and communication. Utilizing quantitative methodology, a survey questionnaire is used to collect data. The implication of this study for policymakers regarding the enhancement of ODL is to maximize student satisfaction by prioritizing essential dimensions. This study’s findings can be utilized by ODL universities to enhance pedagogical dimension, management of atypical situations, academic service delivery, and quality, as well as to guide the implementation of effective ODL strategies.